2020
DOI: 10.7126/cumudj.728154
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Caries Prevalence and Associated Risk Factors Among Turkish Children in Edirne, Turkey

Abstract: Objectives: Dental caries has a multifactorial etiology that has been associated with many risk factors such as improper dietary habits, poor oral hygiene, parental education and socioeconomic status of family. It is essential to identify the potential risk factors to improve the oral health of children. The aim of the present study is to evaluate dental caries prevalence and potential risk factors in a group of Turkish children residing in Edirne province. Materials and Methods: Data of 704 children aged betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Studies from different countries give the results of high prevalence of dental caries in school-aged children. In a study conducted in Turkey, the prevalence of the dental caries in children aged 7–12 years was reported as 68.89% [ 10 ]. Another study conducted among 6–12-year-old children reported the prevalence of dental caries as 81.87% [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from different countries give the results of high prevalence of dental caries in school-aged children. In a study conducted in Turkey, the prevalence of the dental caries in children aged 7–12 years was reported as 68.89% [ 10 ]. Another study conducted among 6–12-year-old children reported the prevalence of dental caries as 81.87% [ 11 ].…”
Section: Introductionmentioning
confidence: 99%